Inhibition of kinesin family member 20B sensitizes hepatocellular carcinoma cell to microtubule‐targeting agents by blocking cytokinesis. Issue 11 (4th October 2018) - Liu, Xinran; Li, Yangkai; Zhang, Xia; Liu, Xin‐Yuan; Peng, Anlin; Chen, Yuchen; Meng, Lijing; Chen, Hong; Zhang, Yu; Miao, Xiaoping; Zheng, Ling; Huang, Kun
Abstract: Kinesin family member 20B (KIF20B, also known as MPHOSPH1) is a kinesin protein that plays a critical role in cytokinesis. Previously, we and others have demonstrated the oncogenic role of KIF20B in several cancers; however, the exact mechanisms underlying its tumorigenic effects remain unclear. Herein, we showed overexpression of KIF20B in human hepatocellular carcinoma (HCC) and reported a negative correlation between KIF20B level and prognosis of patients. Mechanistically, reducing KIF20B blockades mitotic exit of HCC cells at telophase in a spindle assembly checkpoint independent way. Importantly, reducing KIF20B acts synergistically with three microtubule‐associated agents (MTA) to p53‐ or p14ARF‐dependently suppress p53‐wt or p53‐null HCC cells. In addition to taxol, reducing KIF20B also enhanced the toxicity of two chemotherapeutic drugs, hydroxycamptothecin and mitomycin C. In conclusion, we found a novel mechanism in that blocking cytokinesis by KIF20B inhibition increases the efficacy of MTA; our results thus suggested a dual‐mitotic suppression approach against HCC by combining MTA with KIF20B inhibition, which simultaneously blocks mitosis at both metaphase and telophase. Abstract : We found a novel mechanism in that blocking cytokinesis by MPHOSPH1 inhibition increases the efficacy of MTA. Based on this finding, we proposed and validated an effective dual‐mitotic suppression strategy against HCC by combining antimitotic drugs with cytokinesis inhibition, which blocks mitosis at both metaphase and telophase. Moreover, our work raised the possibility that proteins essential for cytokinesis may be considered as potential targets for cancer therapy, especially against SAC‐insensitive cancers.